The effect of Fe as an impurity element for sustainable resynthesis of Li[Ni1/3Co1/3Mn1/3]O2 cathode material from spent lithium-ion batteries. (10th February 2019) - Park, Sanghyuk; Kim, Duho; Ku, Heesuk; Jo, Minsang; Kim, Sangjun; Song, Junho; Yu, Jisang; Kwon, Kyungjung
Abstract: We synthesize Li[Ni1/3 Co1/3 Mn1/3 ]O2 (NCM) and Li[Ni1/3 Co1/3 Mn1/3 ]Fex O2 (NCMF) cathode active materials with various amounts of Fe via hydroxide coprecipitation and calcination processes, which simulate the resynthesis of NCM in leach liquor containing Fe from spent lithium-ion batteries (LIBs). The crystal structure and electrochemical performances of the synthesized NCMF (i.e., NCMF (0.05%), NCMF (0.25%) and NCMF (1.0%)), are investigated and compared with NCM. The structural perfection of NCMF gradually deteriorates with increasing the amount of Fe because of undesirable cation mixing between Ni 2+ /Fe 3+ and Li + sites. In LIB performances, NCMF (0.05%) and NCMF (0.25%) present relatively reduced overpotential leading to superior rate performance at high C-rates to NCM with NCMF (1.0%) having the poorest. In terms of cycling stability, however, capacity retention improves as the Fe content in NCMF increases. The thermal stability of NCM and NCMF is also measured by differential scanning calorimetry, and the post-mortem analysis of X-ray photoelectron spectroscopy reveals that the ratio of Mn 3+ becomes lower after cycling tests as the amount of Fe in NCMF increases. Moreover, the additional post-mortem analysis of energy dispersive spectroscopy on graphite surface after full cell cycling tests further confirms the positive effect of Fe on the improved capacity retention performance of NCMF. Therefore, even if Fe is regarded as an impurity component in the LIB recycling process, a small amount of Fe in the resynthesized NCM cathode material could favor high power and high cycling stability. Highlights: Li[Ni1/3 Co1/3 Mn1/3 ]Fex O2 is made by coprecipitation, simulating resynthesis of NCM. A trace amount of Fe in NCM could improve capacity and rate capability. Excessive Fe in NCM incurs cation mixing, which hinders the migration of Li + ions. Onset temperature for thermal decomposition increases as Fe content increases. The improved cycleability of NCMF is validated by post-mortem analyses.